Perancangan Dashboard Untuk Monitoring Dan Evaluasi (Studi Kasus : FILKOM UB) - Winda Willina Sihombing; Himawat Aryadita; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Faculty of Computer Science (FILKOM) is one of the faculties owned by Universitas Brawijaya. The purpose of this study is to make a dashboard design for student academic monitoring and evaluation. Dashboard is a visualization device that displays visuals of the most important information needed to achieve one or more goals. Dashboard in the research can be used to help the leaders of the study program at FILKOM in monitoring and evaluating performance on the quality services of FILKOM in terms of academic students and student activities by presenting Key Performance Indicators (KPI) information in dashboard. Data displayed in visual form can be analyzed in a more effective, efficient and comprehensive way. The prototype dashboard is built through a user-centric approach with four main stages, namely identification of needs, planning, prototype design and prototype evaluation. Based on the activities carried out, it was concluded that dashboard designed for FILKOM was a strategic dashboard, where a dashboard could display KPI information in an interactive gauge meter, line chart and bar chart with color coding. Appearance of data in graphical form can be easily understood by users, so that the main purpose of information delivery and dashboard design has been reached.